Oxygenolysis of a series of copper(ii)-flavonolate adducts varying the electronic factors on supporting ligands as a mimic of quercetin 2, 4-dioxygenase-like activity. Issue 11 (22nd February 2022) - Podder, Nirmalya; Dey, Subhasis; Anoop, Anakuthil; Mandal, Sukanta
Abstract : Influence of electronic effects on the dioxygenation reaction of copper(ii )-flavonolate adducts, as a functional mimic of quercetin 2, 4-dioxygenase-type reactivity, has been described in this work. Abstract : Four copper(ii )-flavonolate compounds of type [Cu(L R )(fla)] where L R = 2-( p -R-benzyl(dipyridin-2-ylmethyl)amino)acetate; R = –OMe (1 ), –H (2 ), –Cl (3 ) and –NO2 (4 ) have been developed as a structural and functional enzyme–substrate (ES) model of the Cu 2+ -containing quercetin 2, 4-dioxygenase enzyme. The ES model complexes 1–4 are synthesized by reacting 3-hydroxyflavone in the presence of a base with the respective acetate-bound copper(ii ) complexes, [Cu(L R )(OAc)]. In the presence of dioxygen the ES model complexes undergo enzyme-type oxygenolysis of flavonolate (dioxygenase type bond cleavage reaction) at 80 °C in DMF. The reactivity shows a substituent group dependent order as –OMe (1 ) > –H (2 ) > –Cl (3 ) > −NO2 (4 ). Experimental and theoretical studies suggest a single-electron transfer (SET) from flavonolate to dioxygen, rather than valence tautomerism [Cu II (fla − )] ↔ [Cu I (fla˙)], to generate the reactive flavonoxy radical (fla˙) that reacts further with the superoxide radical to bring about the oxygenative ring opening reaction. The SET pathway has been further verified by studying the dioxygenation reaction with a redox-inactive Zn 2+ complex, [Zn(L OMe )(fla)] (5 ).